A Multioutput Cost Function for Port Terminals : Some Guidelines for Regulation - Tovar, Beatriz (World Bank, Washington, DC, 2014)
Cargo handling in ports is a multioutput activity, as freight can arrive in many forms such as containers, bulk, rolling stock, or noncontainerized general cargo. In this paper Tovar, Jara-D, and Trujillo analyze the operation of port terminals through the estimation of a multioutput cost model that uses monthly data on three firms located at the Las Palmas port in Spain. This permits the calculation of product-specific marginal costs, economies of scale (general and by firm), and economies of scope, which are key tools to help the regulators in their task.